2004
DOI: 10.1074/jbc.m309979200
|View full text |Cite
|
Sign up to set email alerts
|

STAT4 Is Required for Interleukin-12-induced Chromatin Remodeling of the CD25 Locus

Abstract: Interleukin 1 is a pleiotropic cytokine produced from macrophages and dendritic cells, which induces several responses in T cells including increased proliferation, increased cytotoxic activity, and Th1 differentiation (1). IL-12 activates several signaling pathways that may mediate these biological activities including p38 MAPK and the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway (2-5). Upon binding of IL-12, both chains of the IL-12 receptor (IL-12R␤1 and IL-12R␤2) heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…It was shown that the T-cell activation marker CD25 may have been improperly induced in response to IL-12 produced by the APCs. Interestingly, it has been shown that signal transducer and activator of transcription 4 (STAT4) is the critical mediator of IL-12-induced expression of CD25 (35) and that STAT4 deficiency in mice is associated with reduced IFN-␥ levels, accelerated nephritis, and increased mortality (24). Another characteristic of the UTI-prone subjects studied here was the lack of correlation between CD54 T-cell surface expression and TNF-␣ production by DCs.…”
Section: Discussionmentioning
confidence: 88%
“…It was shown that the T-cell activation marker CD25 may have been improperly induced in response to IL-12 produced by the APCs. Interestingly, it has been shown that signal transducer and activator of transcription 4 (STAT4) is the critical mediator of IL-12-induced expression of CD25 (35) and that STAT4 deficiency in mice is associated with reduced IFN-␥ levels, accelerated nephritis, and increased mortality (24). Another characteristic of the UTI-prone subjects studied here was the lack of correlation between CD54 T-cell surface expression and TNF-␣ production by DCs.…”
Section: Discussionmentioning
confidence: 88%
“…In T cells, STAT4 ChIP has revealed many genes bound and regulated by STAT4, including Ifng , Il12rb2 , and Il2ra (27, 28). Consistent with a broad role for STAT4 in the initiation of type 1 immune responses, IL-12, together with IFN-α and IFN-β, induces IFN-γ production in antiviral T cells via STAT4 (29).…”
Section: Discussionmentioning
confidence: 99%
“…The implications of enhanced signaling of the IL-12Rb2 pathway on the function or generation of TCDD-CD4 + cells is currently under investigation. Because IL-12-responsive elements can cause chromatin remodeling at the CD25 gene locus and increase CD25 expression (43), IL-12 signaling may be an important pathway for up-regulating CD25 on TCDD-CD4 + cells. The JAK2/STAT4 pathway is also important in the promotion of IFN-γ production; however increased expression of IFN-γ at the transcript or protein level in TCDD-CD4 + cells was not found.…”
Section: Discussionmentioning
confidence: 99%